Distribution and Ecologica Risk of Sediment Heavy Metals in the Water-Level-Fluctuation Zone of the Shawan River Section of Yelang Lake - Xiaojuan Zhang; Yutao Zhang (Journal of Chemistry)
With the aim of revealing the potential ecological risk and distribution characteristics of heavy metals on the surface sediment at the Shawan River section of Yelang Lake, the following three analyses were first performed: (1) analysis of grain-size composition on sediment samples collected at seven different sites in the water-level-fluctuation zone (WLFZ); (2) analysis of bulk sediment content of six heavy metals, namely, Cd, Cr, Pb, Mn, Zn, and Cu; and (3) the correlation analysis of grain-size composition and heavy metal content in the sediment. Afterwards, the approach of Hakanson potential ecological risk index was employed to analyze the risk of heavy metal pollution in sediments of seven WLFZ plots. The outcomes indicate that (1) the mean sediment grain size at each sampling site was generally >0.063 mm, with gravel grains (>1 mm) and sand grains (0.22–1 mm) accounting for the largest proportions; (2) the site-averaged mean sediment content of each of the six heavy metals was significantly higher than their respective geochemical background contents in the sediment of Guizhou Province, and the grain-size dependence of the bulk sediment content of heavy metals was not significant; (3) the distribution of Cr was relatively independent of other metals, which was in contrast to notable positive correlations observed between other metals; and (4) in accordance with the approach of Hakanson potential ecological risk index, for these heavy metals, their potential ecological risk reduced by the order of Zn < Cr < Cu < Pb < Cd, with Cd having a mean potential risk index (Ei) of 566.13, suggestive of a very high level of potential ecological risk, Zn, Cr, and Cu having a mild potential ecological risk, and Pb having moderate potential ecological risk. Cd largely contributes to the comprehensive ecological risk index RI is the largest, thereby having important environmental implications.